Figures of speech in the discourse of British tabloids - Slezáková, Šárka (Univerzita Pardubice, 2010)
This work focuses on occurences of figures of speech in the discourse of British tabloids press. Figures were found in selected articles from four different British tabloids. This work also deals with the language of newspapers and the figurative language itself.
Básnické tropy v diskurzu novinových clánku britského bulvárního tisku
Keywords: básnické tropy; diskurz Britského bulvárního tisku; básnický jazyk; novinový jazyk; figures of speech; discourse of British tabloids; figurative language; language of newspapers